Pelatihan Pemanfaatan Media Sosial Untuk Pengembangan UMKM Kerupuk Beras Di Kelurahan Rabangodu Selatan - Muhlis Ade Putra; Nurlita Apriyanti; Febi Febrianti; Irma Suciati; Nurfitriah Ningsih Magfiratus Sholeha; M. Fitrah Anjani; Aris Munandar (Universitas 45 Surabaya, 2024)
Training on the Use of Social Media for the Development of RICE CRACKERS MSMEs IN SELATAN RABANGODU VILLAGE. Training on the Use of Social Media for the Development of Rice Cracker MSMEs in South Rabangodu Village is a program that aims to provide understanding and skills to rice cracker MSME owners in South Rabangodu Village in utilizing social media as a tool for developing their business. In an increasingly advanced digital era, the use of social media has become very important for MSMEs to increase their visibility, marketing and presence in the digital world. This training will help rice cracker MSME owners in Rabangodu Selatan Subdistrict to understand the importance of social media in marketing their products. The training material includes effective social media marketing strategies, creating interesting and relevant content, and managing social media accounts well. Trainees will be taught how to utilize social media to reach a wider audience, interact with potential customers, and build closer relationships with them. In addition, participants will also learn about special social media features that can be used to improve product marketing, such as paid advertising, product promotions, and performance analysis. By utilizing these features, it is hoped that rice cracker MSMEs in Rabangodu Selatan Subdistrict can increase the visibility of their products and reach a wider audience. By participating in this training, rice cracker MSME owners in Rabangodu Selatan Subdistrict are expected to be able to increase their presence in the digital world, increase sales and expand their market reach. This training also provides an opportunity for participants to expand their knowledge and skills in utilizing social media for the success of their business.